Antimalarial Herbal Plants in Kupang, Indonesia - Ihwan Ihwan; Sari Hauliah Ahmad Koda (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Malaria is an infectious disease caused by Plasmodium parasite transmitted through female Anopheles mosquito bite. This disease is harmful because Plasmodium is known to be resistant to antimalarial drugs. The emergence of malaria resistance has raised concerns among researchers to look for any alternative antimalarial drugs. There are some plants potentially used as antimalarial drugs that should bewell-documented through scientific research. This study aimed to get to know plant species that has antimalarial activity in Kupang region. Method: This research applied qualitative descriptive method while using exploration method specifically in the sampling process. Every sample is then taken for preservation as herbarium and identified based on its morphological features using determination key handbook. The result showed that there are 17 species of antimalarial plant in 10 observational sites. Those species of antimalarial plants i.e. Tithonia diversifolia, Momordica charantia, Cyperus rotundus, Strychnos lingustrina, Andrographis paniculata, Callicarpa longifolia, Tinospora crispa, Piper betle, Plectranthus scutellarioides, Alstonia scholaris, Carica papaya, Amaranthus spinosus, Artocarpus champeden, Cassia siamea, Azadirachta indica, Helianthus annuus and Blumea balsamifera. Therefore, the availability of the plant species with antimalarial activity in Kupang needs to be explored and developed as an alternative approach for the society in treating Malarial diseases.